2023
DOI: 10.3389/fmicb.2023.1285445
|View full text |Cite
|
Sign up to set email alerts
|

Stability of soil bacteria in undisturbed soil and continuous maize cultivation in Northern Thailand

Noppol Arunrat,
Chakriya Sansupa,
Sukanya Sereenonchai
et al.

Abstract: Rotational shifting cultivation (RSC) in Northern Thailand serves the dual purpose of ensuring food security and meeting economic goals through maize cultivation. However, the research question remains: Does the dynamics of soil bacterial communities differ between maize monoculture and RSC fields with continuous fallow throughout the season? Therefore, the objective of this study was to investigate and compare the variation of soil bacterial communities in maize monoculture and fallow RSC fields. A continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 90 publications
3
2
0
Order By: Relevance
“…These findings underscore the complex relationship between soil properties and microbial responses to fertilizer treatments. Data obtained are in line with findings of Arunrat et al [40], showing that over a 5-year period, the application of fertilizer and tillage practices significantly contributed to an augmentation in the diversity and richness of soil bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…These findings underscore the complex relationship between soil properties and microbial responses to fertilizer treatments. Data obtained are in line with findings of Arunrat et al [40], showing that over a 5-year period, the application of fertilizer and tillage practices significantly contributed to an augmentation in the diversity and richness of soil bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…These findings underscore the complex relationship between soil properties and microbial responses to fertilizer treatments. Our data agree with the findings of Arunrat et al [55], showing that over a 5-year period, the application of fertilizer and tillage practices significantly contributed to an augmentation in the diversity and richness of soil bacteria. Regarding bacterial abundance, it was strongly influenced by organic matter (OM) and organic carbon (OC).…”
Section: Effect Of Different Fertilizers On Soil Qualitysupporting
confidence: 92%
“…These observations highlight the intricate interplay between soil characteristics and the microbial shifts following fertilizer application. The findings align with the research conducted by Arunrat et al (2023) [40], which demonstrated that consistent fertilizer use and tillage methods over five years markedly enhanced the diversity and abundance of soil microbial communities.…”
Section: Compost Effects On Soil Chemical and Biological Propertiessupporting
confidence: 90%